Las prácticas de "doble rol" en los gobiernos corporativos de empresas chilenas - de la Vega, Orlando (2005)
This project is an exploratory investigation on the malpractices of corporate government associated with the «double role» that some shareholders assume in a private or public company (totally or partially state-owned). We will try to discover the various generic forms that these malpractices adopt, as well as explore the positive or negative perceptions that they generate on the Chilean corporate or institutional shareholders. Next, we will examine various alternatives to confront them (by reducing their occurrence or eliminating them) in order to improve the practices of corporate government in Chile.